1997
DOI: 10.1006/viro.1997.8656
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Epidemiology of Human Immunodeficiency Virus Type 1 in Six Cities in Britain and Ireland

Abstract: We have sequenced the p17 coding regions of the gag gene from 211 patients infected either through injecting drug use (IDU) or by sexual intercourse between men from six cities in Scotland, N. England, N. Ireland, and the Republic of Ireland. All sequences were of subtype B. Phylogenetic analysis revealed substantial heterogeneity in the sequences from homosexual men. In contrast, sequence from over 80% of IDUs formed a relatively tight cluster, distinct both from those of published isolates and of the gay men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 36 publications
0
24
0
4
Order By: Relevance
“…The broadest pattern observed was the strong separation between the transmission clusters dominated by MSMs and those dominated by IDUs and HETs. Separation of IDUs from other transmission groups (mainly MSMs and hemophiliacs) has previously been found in a number of smaller studies [9,10,25,26], whereas an association between IDUs and HETs has only been documented for a fairly small study based on patients from Edinburgh [9]. On top of this broad separation, we have found a weaker but still substantial exchange between HETs and MSMs, which has not been found in previous molecular epidemiology studies.…”
Section: Discussionmentioning
confidence: 34%
“…The broadest pattern observed was the strong separation between the transmission clusters dominated by MSMs and those dominated by IDUs and HETs. Separation of IDUs from other transmission groups (mainly MSMs and hemophiliacs) has previously been found in a number of smaller studies [9,10,25,26], whereas an association between IDUs and HETs has only been documented for a fairly small study based on patients from Edinburgh [9]. On top of this broad separation, we have found a weaker but still substantial exchange between HETs and MSMs, which has not been found in previous molecular epidemiology studies.…”
Section: Discussionmentioning
confidence: 34%
“…It is therefore much more likely that the phylogenetic mixing is the result of IDUto-IDU transmission among the sampled populations. A similar observation of phylogenetic mixing has been demonstrated for HIV infection of IDUs from different cities in the United Kingdom and Ireland [25] and from different European countries [26]. In the former report, the authors found no clear evidence of segregation of sequences on the basis of city or country of origin, whereas, in the latter, segregation evident early in the epidemic was found to be progressively lost over time.…”
Section: Discussionmentioning
confidence: 57%
“…In the United Kingdom, HIV-1 was first identified during the 1980s among MSM with all identified strains belonging to B clade (Brown et al, 1997;I,, 1988;Wade et al, 1998). However, the pattern in heterosexual groups is changing with a steady increase in the number of non-B clades since the 1990s (Hughes et al, 2009) and has mainly been associated with sub-Saharan African and South American immigration (de Oliveira et al, 2010;Fox et al, 2010; United Kingdom Collaborative Group on HIV Drug Resistance, 2014).…”
Section: Western Europementioning
confidence: 96%